Norepinephrine as a marker of recovery after intense training in elite swimmers - Hooper, S.; MacKinnon, L. T.
The data suggest that recovery after intense training can be monitored during tapering and that an accurate prediction of improved performance may be possible if a range of physiological and psychological variables are measured. The results also suggest that further investigation is warranted regarding norepinephrine as a monitoring tool during tapering for major competition.